Creative Destruction? Impact of E-Commerce on the Retail Sector - Chava, Sudheer; Oettl, Alexander; Singh, Manpreet; Zeng, Linghang (Management Science, 2024)
Using an administrative payroll data set for 2.6 million retail workers, we find that the staggered rollout of a major e-commerce firm’s fulfillment centers reduces traditional retail workers’ income in geographically proximate counties by 2.4%. Wages of hourly workers, especially part-time hourly workers, decrease significantly driven by a drop in the number of hours worked. We observe a U-shaped pattern in which both young and old workers experience a sharper decrease in wage income. Consequently, some workers experience an increase in credit card delinquency. Using data for 3.2 million stores, we find that sales (employment) at proximate stores decrease by 4% (2.1%). Exits, especially of young and small stores, increase, and entry decreases. Our results highlight how creative destruction led by e-commerce impacts local labor markets. This paper was accepted by Anindya Ghose, information systems. Funding: The authors gratefully acknowledge funding support from the Kauffman Foundation Junior Faculty Fellowship. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4795 .